INITIAL TRAINING, PEDAGOGICAL PRACTICE, BEGINNER TEACHER AND THE PROCESS OF BECOMING A TEACHER - Amorim, Aline Diniz de [UNESP]; Silva Fernandes, Maria Jose da [UNESP] (Univ Estadual Sudoeste Bahia, 2018)
This text has as gol discuss the potentialities and fragilities of teacher initial training having as reference the pedagogical pratice. The polyvalent teacher who act in the early years of Elementary School and Childhood Education, before to be considered how experienced, has a long way over of his time in teaching. The concerns and yearning from early in his career are engendered mostly by weakness of the initial training that not always focused the teacher practice in classroom. To analysis the potentialities and fragilities of teacher initial training and the ways that it helps the teacher initiation, we embased on collecting datas from interviews with six beginning teacher - in the first five years of action in profession - graduates of Pedagogy in a public study institution from Sao Paulo state. As main results of the search it was found that the beginning teachers recognized initial training as fundamental to the preparation for the exercise of teaching, however, the teachers pointed limits of this training, highlight especially the devaluation of the profession practice dimension which should be additional to the theoretical formation. The respondents faced major challenges when arrived the scholar environment. With this challenges, the teachers also occurred significant learning with regard to exchanges of experience with experienced teachers and with the management team, which indicates the relevance of the practice for the professional acting. In this way, the research pointed out the massive fragility of pedagogical practice dimension of initial training, indicating that the research results have not been adequately incorpored into teacher preparation.
Keywords: Beginner teacher; Pedagogical practice; Teachers training